"Yeah that Made a Big Difference!": The Importance of the Relationship between Health Professionals and Fathers Who Have a Child with Down Syndrome. Issue 3 (20th November 2017) - Docherty, Freyja; Dimond, Rebecca
Abstract: Evidence suggests that medical services do not reflect the increased involvement of fathers in childcare, a discrepancy that can often lead to feelings of exclusion and inequality. Fathers who have a child with Down syndrome may encounter many different health professionals during their child's life, therefore it is important to consider this relationship, and investigate the factors that influence their experiences. This is particularly important because the limited research focusing on fathers suggest that those who have a child with Down syndrome can experience increased stress levels and lasting feelings of loss and grief. It is therefore important to address their relationships with health professionals, as these may be a significant resource to prevent these feelings. This study used interpretative phenomenological analysis (IPA) to explore the experiences of seven fathers who have a child with Down syndrome, focusing on their interactions with health professionals. The analysis showed that the major factors associated with negative experiences were feelings of exclusion, receiving overly negative information about the condition and a perceived lack of on‐going support. Positive experiences were associated with being made to feel like an equal parent, being given direct/clear information and being congratulated on the birth of their child. These results provide an insight into what fathers expect in terms of their own and their child's care and highlight that health professionals have an important and extensive role in influencing fathers' experiences of Down syndrome.